Patient Safety Policies and Practices among Selected Middle East Countries: Are We Walking on the Right Path? By Madani (2023) - Alharbi, Mohammed (International Journal of Innovative Research in Medical Science, 2023)
Human errors have always been a primary topic of discussion in complex systems, especially in the healthcare industry due to the adverse ramifications not only on the patient but also on the involved healthcare practitioner through cultural blame. Concisely, medical errors have adverse effects on patient safety policy and treatment quality, and it also exacerbates financial hardship. As a result, individuals continue to be wounded and receive substandard care. However, this situation is entirely avoidable if healthcare organizations have access to and are aware of accurate healthcare data. Therefore, this backdrop predicates the need for the promulgation of public safety policies and practices, primarily in Middle East Countries where human error has been prevalent.